O pop rock brasileiro nos anos de 1980: mídia, produção de sentidos e a representação de uma geração - Feitosa, Therence Santiago Alves (2018)
The present investigation focuses on analyzing some songs produced in the 1980s by the bands Legião Urbana, Titãs, Barão Vermelho and Engineers of Hawaii. The research, through the lenses of pop rock, presents discussions about some cultural, social and political scenarios that were part of Brazil at that time. The idea is to develop "certain cartographies" of the period, from analyzes of the internal structures and contents of the lyrics of these songs. The thesis intends to show the pop rock of the 1980s, as a translating instrument in relation to what some young people (rockers) lived at the time. A part of the Brazilian media of that moment "discovered" this "new" phenomenon and dedicated itself to divulge this musical genre (BASTOS, 2005). The 1980s in Brazil were presented as a period of clear transition, since in that decade a military dictatorship that lasted approximately 20 years ended (RAMOS, 2010). In the music scene a genre gained strength, voice and form: pop rock. As a hypothesis it is possible to argue that it is precisely in the cultural spheres that symbolically the daily relations are configured (LÓTMAN, 1981), that is, in day-to-day practices, space is opened for representations, as well as for the construction of series of languages. According to Lótman (1978), every artistic work is within its own context of producing subjectivity. Barbero (2013) advocates communication as a process, therefore, it is understood that the communicative nature happens in a fluid way, in constant and intertwined movements that transpose in the scope of culture. At that moment there were several dialogues between media, artists and the public, this took place in miniature movements that approached subjects of culture, objects of culture and nature / environment. In this thesis, it is intended to propose how the context of the songs were related to certain processes of exploitation of the different materials of the culture available in Brazil. As theoretical foundation, research of a qualitative nature is mainly used as references of the semiotics of culture, communication and anthropology